ANALISIS REPRESENTASI MATEMATIS SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA BERDASARKAN TAHAPAN KRULIK DAN RUDNICK DITINJAU DARI ADVERSITY QUOTIENT - DEWI, SETYA (Kadikma, 2021)
This research purpose to describe the mathematical representation abilities of students based on the Krulik and Rudnick stages in terms of students' AQ. This research type is qualitative descriptive research. The research location is in SMAN Darussholah Singojuruh with the subjects of class XI MIPA 3 and XI MIPA 7 as many as 30 students. The data collecting methods used test and interview methods, with research instruments, such as Adversity Response Profile (ARP) questionnaire, mathematics test questions on linear program material, interview guidelines, and validation sheets. The subjects selected as interview respondents were two students from each level of AQ who had significant differences in ARP scores (scores between AQ Climber, Camper, and Quiter), as well as based on the timeliness and accuracy of students' answers. Based on the test result data analysis and interview data analysis, the following results were obtained, such as 1) Climber students could solve linear program questions based on Krulik and Rudnick stages coherently, and be able to used forms of verbal representations, visual representations, and mathematical expressions properly and correctly; 2) Camper students could solve linear program questions based on Krulik and Rudnick stages coherently but had not been able to use forms of verbal representations, visual representations, and mathematical expressions properly and correctly; 3) Quitter students had not been able to solve linear program questions based on Krulik and Rudnick stages correctly and had not been able to use their verbal representation, visual representation, and mathematical expression skills properly.